Family Experiences of Out-of-Hospital Deaths Where Ambulance Services Respond in Aotearoa New Zealand - Satchell, Eillish; Gott, Merryn; Dicker, Bridget; Moeke-Maxwell, Tess; Anderson, Natalie E (SAGE Publications, 2025)
Background: As ambulance services respond to a growing number of out-of-hospital deaths, supporting bereaved families is increasingly recognised as an important aspect of paramedic care. Actions from ambulance personnel can significantly shape family experiences, underscoring the need for compassionate, evidence-based care in the event of a death. However, currently, little is known about the needs and perspectives of families during these events, particularly from Indigenous and culturally diverse populations. This study explores the experience of Māori and non-Māori families from Aotearoa New Zealand who were present at a death where emergency ambulance services responded. Methods: This qualitative study, underpinned by kaupapa Māori research principles, explored family experiences of emergency ambulance care in the context of a death. Participants were recruited through purposive volunteer sampling, with invitations shared via local and social media. Semi-structured interviews employed a collaborative storytelling approach, where researchers and families co-constructed digital narratives of their experiences. Data were analysed using Braun and Clarke's reflexive thematic analysis. Results: We conducted 21 interviews with 23 bereaved family members. Families described having emotional, cultural and spiritual needs during out-of-hospital deaths. Four themes influenced the experiences of family. Making space for family highlighted the importance of meaningful presence and shared decision-making. Compassionate family care reflected the positive impact of compassionate actions. Communication, which was clear and timely, assisted family understanding. Finally, closure in crisis revealed how follow-up support is needed to help families process and accept death. Conclusion: Care that centres empathy, shared decision making, clear communication and responsiveness to individual family needs can improve the experiences of bereaved families. Greater consideration of family needs during resuscitation and its termination is needed to challenge current care paradigms, which equate family presence with family support. Enhancing cultural and spiritual responsiveness offers an opportunity to provide more holistic and culturally safe bereavement care.
Keywords: 4203 Health Services and Systems; 42 Health Sciences; Emergency Care; 8.1 Organisation and delivery of services; Generic health relevance; paramedicine; resuscitation; family; out-of-hospital; death